Rapid Review on the Associations of Social and Geographical Isolation and Intimate Partner Violence: Implications for the Ongoing COVID-19 Pandemic - Mojahed, Amera; Brym, Stephanie; Hense, Helene; Grafe, Bianca; Helfferich, Cornelia; Lindert, Jutta; Garthus-Niegel, Susan (Frontiers in Psychiatry, 2021)
While the COVID-19 pandemic forced millions of people to stay home and minimize their social contacts, newspaper reports worldwide raised concerns as they reported an increasing rate of intimate partner violence (IPV). One link of the measures enforced to control the pandemic to IPV might be a possible side effect of those measures, namely social and geographical isolation. As there was no scientific data investigating the association of IPV and social and geographical isolation in the context of epidemics or pandemics at the time of conducting this rapid review, we aimed at investigating a broader range of contexts of social as well as geographical isolation and its association with IPV to draw conclusions regarding the COVID-19 pandemic. We searched Embase, PubMed, PsycINFO, and Web of Science (core collection). A research strategy was developed and observational studies were included if they considered men and/or women, estimates of social and geographical isolation, and IPV as a primary outcome. Of the 526 identified studies, eleven were included in this review. The included studies involved 15,695 women and were conducted in the USA, Sweden, Ethiopia, Egypt, Spain, and Turkey. Indicators of social isolation such as lack of social, emotional, or informational support or the frequency and quality of social contacts were narratively assessed. Geographical isolation was primarily assessed by physical distance to the next town or support service. Both social and geographic isolation were found to be associated with an increased risk of IPV. Recommendations made by the individual studies include the following: a) improving access to social networks outside the victims’ own group, b) improving their economic circumstances, c) asserting the responsibility for those in contact with the victims, and d) increasing the focus on access to preventive services and programs need to be taken into account. Therefore, considering the particular infrastructure and legislation of the countries affected by the pandemic, policies need to ensure constant access to shelters and other help services and increase awareness for IPV in the society. In addition, future studies are warranted to assess prevalence rates and risk factors of IPV during the COVID-19 pandemic.